(1+y)(2y+3)=0

Simple and best practice solution for (1+y)(2y+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1+y)(2y+3)=0 equation:



(1+y)(2y+3)=0
We add all the numbers together, and all the variables
(y+1)(2y+3)=0
We multiply parentheses ..
(+2y^2+3y+2y+3)=0
We get rid of parentheses
2y^2+3y+2y+3=0
We add all the numbers together, and all the variables
2y^2+5y+3=0
a = 2; b = 5; c = +3;
Δ = b2-4ac
Δ = 52-4·2·3
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1}=1$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-1}{2*2}=\frac{-6}{4} =-1+1/2 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+1}{2*2}=\frac{-4}{4} =-1 $

See similar equations:

| 40x35=4000 | | 20t^2-41t+20=0 | | 16.24-8x=6 | | s/4=53.40 | | 52=y/7 | | 6c-4c=10 | | 1/6=n/32 | | Y=9x+5000 | | 1000000=2000(3)^x | | (3x+1)=43 | | 6.8x-3=5.8x3 | | 50=100+2x | | 0.1^n=0.3 | | x+64+71=180 | | 75-(6x+7)=6(x+7)+x | | 7x2.43=17.01 | | (2x+6)/5=4x-3 | | -19x-12=-169 | | 17x-19=-155 | | x/3-18=42 | | 4u-8.7=4.1 | | 9m-4(2m-3)=5(m+2) | | 18x+6=132=180 | | 4x+10=X+11+2x+14 | | 8n-1(5n+13)=7 | | 3(2a+5)-7=2(4a-5)+3a | | 7x+14=4x+11+2x+24 | | 35=4x-17(2x) | | (78)+(3x-12)=(6x+12) | | 4r-5=2(2r-1)-3 | | (6x-10)=(4x+6) | | 3x3-3x=0 |

Equations solver categories